Analisis Pengelolaan Kas Untuk Penyusunan Laporan Kas pada Toko DK Family - Risca Olivianti; Inung Vias Dras Tistian Hening Tyas; Sri Rahayuningsih (CV. ITTC INDONESIA, 2025)
Cash is one of the current assets that plays an important role in maintaining the smooth operation of a business. DK Family Store, as a retail business, requires a good cash management system so that the flow of receipts and expenditures can be controlled and accurate cash reports can be generated. This study aims to analyze cash management at DK Family Store in order to prepare regular and transparent cash reports. The method used is descriptive analysis by examining the practice of recording cash receipts and expenditures at the store. The results of the analysis show that cash management is still simple and manual, which risks causing errors in the recording of cash receipts and expenditures. The method used is descriptive analysis by examining the practices of recording cash receipts and expenditures at the store. The results of the analysis show that cash management is still simple and manual, which risks causing recording errors. Systematic preparation of cash reports can help store owners know their actual financial position, control cash flow, and facilitate financial decision-making. The recommendations provided are the use of a simple cash recording application and discipline in storing transaction evidence so that the preparation of cash reports is more effective and accurate.